Pembelajaran IPA Berbasis Problem Based Learning untuk Meningkatkan Kemampuan Berpikir Kritis Siswa Kelas V SDSI Amalia - Nurul Azizah; Ekayanti (Kilau Publishing, 2024)
This study aims to assess the impact of implementing Problem-Based Learning (PBL) in enhancing the critical thinking skills of fifth-grade students at SDSI Amalia. In an effort to implement Science learning based on Problem-Based Learning (PBL), this research utilized a classroom action research method with a research subject consisting of 12 students in SDSI Amalia. Data was collected through observation, practice, and analysis of documents related to the implementation of Problem-Based Learning (PBL) to enhance the critical thinking skills of fifth-grade students at SDSI Amalia. Observations were conducted by Supervisor 2 during the learning process, and the researcher practiced teaching students to gain a subjective perspective. Based on the data results achieved, there was an improvement in the learning process. In the pre-cycle, 3 students completed the task with a percentage of 25%, in cycle I this number increased to 10 students completing the task with a percentage of 83.33%, in cycle II all students completed the task with a score above the Minimum Completion Criteria (MCC). Therefore, it can be concluded that the implementation of Problem-Based Learning (PBL) is effective in enhancing the critical thinking skills of fifth-grade students at SDSI Amalia. This reaffirms the importance of student-centered, collaborative learning methods that encourage creative problem-solving.